The potential of onomatopoeia from Javanese culture as assets for visual work creation - Mataram, Sayid; Ranu Wicaksono, Arif; Irfan Ismail, Anugrah; Ardhianto, Peter (Gelar: Jurnal Seni Budaya, 2024)
Onomatopoeia is one of the visual elements in graphic design works. Cultural diversity in Indonesia has the potential to produce domestic onomatopoeia. Antawacana is one of the speech cultural activities of natural sound mimesis in Javanese society. It is the speech and sounds performed by Dalang of Wayang Purwa (puppeteers of shadow puppet performance). This research examines the potential of Indonesian domestic onomatopoeia, especially Javanese, which comes from the speech of puppeteers as an asset to support the increase in potential and productivity in the field of graphic design. This research converts audio into visual items to develop Indonesian domestic onomatopoeia based on the domestic cultural asset of Antawacana. This research interprets sound into visuals by using Antawacana as the basis for visualization. The variety of sounds in Antawacana itself results from Dalang’s interpretation. This research contributes to the Indonesian creative industry by providing visual assets based on Antawacana. These assets can assist the communication process in other creative works. In addition, along with technological developments, the potential of onomatopoeia as a domestic cultural asset can be developed into an artificial intelligence asset in online graphic design creation platforms.